Oral health and systemic health outcomes: A call for interdisciplinary action - Moritz Kebschull; Ryan T. Demmer; Nigel Pitts; Huda Yusuf; Gitana Rederiene; Nikolaos Donos; Wim Teughels; Raman Bedi; Orsolya Nemeth; Mia Rakic; Stéphanie Tubert‐Jeannin; Raimondo Ascione; et al. (Periodontology 2000, 2026)
Abstract Objectives To make the case, from periodontology and dental public health, for interdisciplinary action on oral and systemic health, and to set out recommendations for practice, policy, education, and research. Materials and Methods A joint working group of the European Federation of Periodontology (EFP) and the European Association of Dental Public Health (EADPH), with public‐health stakeholders and delegates from organized medicine (the World Heart Federation, WONCA Europe and the European Forum for Primary Care), synthesized the epidemiological, mechanistic, preventive and health‐systems evidence, and developed consensus recommendations. Results Oral diseases affect around 3.5 billion people and share modifiable risk factors (free sugars, tobacco, and alcohol) and social and commercial determinants with the major non‐communicable diseases (NCDs); inadequate oral hygiene is an additional oral‐specific factor. This argues for integrating oral health into general health through a common risk factor approach rather than disease silos. Periodontitis has the strongest evidence for systemic interactions and, unusually among oral diseases, its treatment improves glycemic control in diabetes and inflammatory or vascular surrogates, though evidence for major clinical events remains limited; other links rest largely on shared risk factors and mechanisms (an asymmetry of evidence, not of public‐health importance). Prevention and integrated care remain under‐implemented. Conclusions Oral health must be recognized as integral to general health and embedded within NCD strategies and universal health coverage through interprofessional, intersectoral action that also tackles the social and commercial determinants and reduces inequalities. Clinical Relevance Equipping all health and social‐care professionals to promote oral self‐care, screen and refer, and prioritize periodontal prevention and treatment, can improve both oral and systemic outcomes.